CO2 + Methanol + Glycerol: Determination of the Compositions in VLLLE From a Synthetic Method-Based Experiment/Theoretical Procedure - Carrera, Gonçalo Valente da Silva Marino (2019)
The experimental synthetic-based method is a straightforward procedure to obtain a complete resolution of the phase behaviour of VLE of binary mixtures; however, it has limited applicability for multicomponent mixtures/multiphase phenomena. The analytical method is an alternative that offers a reasonable solution for complex configurations, however, the investment of time and resources is high. A straightforward alternative presented in this work consists on the application of the synthetic method allied to a theoretical procedure in order to obtain the composition of the existent phases in equilibrium in complex system’s configurations. The case study is a CO2 + methanol + glycerol mixture that at concrete conditions of global composition, pressure and temperature leads to VLLLE. The composition of each phase in equilibrium was determined using the Peng-Robinson EOS with Mathias-Klotz-Prausnitz mixing rule allied to a combination algorithm to find and check the suitable arrangement of derived compositions that respect the thermodynamic criteria of equilibria, balance of masses and order of densities. A single solution was obtained and discussed along the manuscript.